2021
DOI: 10.2196/26670
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Success of Patients’ Continuous Use of Mobile Health Services for Self-management of Chronic Conditions: Model Development and Validation

Abstract: Background Mobile health services are gradually being introduced to support patients’ self-management of chronic conditions. The success of these services is contingent upon patients’ continuous use of them. Objective This study aims to develop a model to measure the success of patients’ continuous use of mobile health services for the self-management of chronic conditions. Methods The proposed model was der… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“… 12 , 13 m‐Health to support patients with chronic diseases in self‐management has been widely considered in the last decade. 14 , 15 WHO defines m‐Health as a medical and public health approach supported by mobile devices, patient monitoring devices, personal digital assistants (PDAs), and other wireless devices. 2 Statista website shows that the m‐Health market is growing and projected to exceed US$ 300 billion by 2025.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 , 13 m‐Health to support patients with chronic diseases in self‐management has been widely considered in the last decade. 14 , 15 WHO defines m‐Health as a medical and public health approach supported by mobile devices, patient monitoring devices, personal digital assistants (PDAs), and other wireless devices. 2 Statista website shows that the m‐Health market is growing and projected to exceed US$ 300 billion by 2025.…”
Section: Introductionmentioning
confidence: 99%
“…m‐Health applications facilitate communication between patients and treatment staff, reduce chronic diseases costs, adhere to medical regimens, and influence patient outcomes. 14 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile health services are a supportive technique that has gradually been introduced to support patients in their self-management of chronic disorders, such as hypertension [ 10 ], cardiovascular diseases [ 11 ], diabetes [ 12 ], and obesity [ 13 ], and even improve patients’ medication adherence [ 14 ]. Recently, some smartphone apps were designed to address the COVID-19 pandemic [ 15 ], while an evidence-based mobile health (mHealth) program led to significant reductions in depressive symptoms [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…To fully utilize the collected information, inducing long-term usage by the user is needed. Only a handful of previous studies focused on the continued use of mPHR services [ 13 , 14 , 15 , 16 ]. One study reported that it is important for mobile app users to frequently enter data into the app to monitor health-related behaviors for effective weight loss, regardless of the region and app version [ 14 ].…”
Section: Introductionmentioning
confidence: 99%